List edge and list total coloring of planar graphs without intersecting 8-cycles. (18th May 2020) - Zhang, Wenwen; Li, Ye
Abstract: In this thesis, given a planar graph G containing no intersecting 8-cycles, we obtain χ l '( G )= k and χ "l ( G ) = k + 1 for k = max10, Δ( G ).